Controle tecnológico de obras rodoviárias envolvendo a reciclagem in situ de bases granulares de pavimentos asfálticos - Sachet, Taís (2007)
This work presents the results of a study intended the obtaining and introduction of the auxiliary elements to assure the road pavements technological control of rehabilitation which involves the recycling in place of granular bases. This verification was made using two techniques, the CBR in place verification, through the use of DCP (Dynamic Cone Penetrometer), and the granulometric framing, through the curve of Talbot, for recycled materials. The investigations were accomplished starting from practical applications in roads in the north of the state of Rio Grande do Sul, which involved, in an experimental way, the pavements rehabilitation through the base course recycling, incorporating the surface layer. The recycled granular base behavior was verified starting from DCP, gradation (curve of Talbot), CBR and density in place tes. The tests intervals and frequency, for granular base execution, was defined based on the observance to imposed demands of the Infrastructure Transports National Department (DNIT) specification service. Finally, through the data processing obtained in the tests, it was possible the elaboration of the technical specification proposal. The presented conclusions, through the obtained results in the field tests, demonstrate that the use of DCP has been shown highly positive, being a low cost and easy execution technique. The measures proposed for the recycled granular bases technological control, when applied on pavements rehabilitation works, have been showed effective, assuring the recycled bases structural adaptation